Sistem Pengarsipan Kantor PSW YPPK Nabire Berbasis Web - Marselino Marthen Yogi; Ester Ayuk P; Cici Kamalia (Jurnal Teknologi dan Informatika, 2024)
The Web-Based YPPK Nabire PSW Digital Archiving Application is an information technology innovation that aims to improve the efficiency and effectiveness of the filing process at the Nabire Catholic Education and School Foundation (YPPK). This article discusses the implementation and development of web-based digital archiving applications to replace existing traditional archiving systems. The application is designed to simplify the process of managing and searching archived documents through a user-friendly web interface. By using web technologies namely PHP programming language and CSS Boostrap. Users can access and manage digital archives more quickly and efficiently. In addition, this application also provides security features to protect the confidentiality and integrity of archive data. This application development methodology involves analyzing user needs, intuitive interface design, and implementing a reliable database system. The article also highlights the benefits of digital archiving applications, including time savings, reduced printing costs, and improved information accessibility. With the implementation of YPPK Nabire's Web-Based PSW Digital Archiving Application, it is expected that YPPK Nabire can gain significant benefits in effectively managing and utilizing archive data, supporting better decision making, and improving overall organizational performance.